2015
DOI: 10.1186/0717-6287-48-2
|View full text |Cite
|
Sign up to set email alerts
|

Sugars, organic acids, and phenolic compounds of ancient grape cultivars (Vitis vinifera L.) from Igdir province of Eastern Turkey

Abstract: BackgroundThe Eurasian grapevine (Vitis vinifera L.) is the most widely cultivated and economically important horticultural crop in the world. As a one of the origin area, Anatolia played an important role in the diversification and spread of the cultivated form V. vinifera ssp. vinifera cultivars and also the wild form V. vinifera ssp. sylvestris ecotypes. Although several biodiversity studies have been conducted with local cultivars in different regions of Anatolia, no information has been reported so far on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 17 publications
6
81
2
2
Order By: Relevance
“…Vitamin C content (JU_VC) ranged between 9.7 ± 1.2 (cv. Muscat of Alexandria) and 30.9 ± 0.3 mg/100 mL (Halawani Kanawat), a similar range of variation to that previously reported for a set of autochthonous table grape cultivars from Turkey (Eyduran et al 2015). Besides, some of the qualitative traits analyzed did not show any variance in our set of cultivars: BE_FS (all cultivars were seeded), LE_PSLV (all cultivars presented veins in both sides of the leaf petiole sinus), LE_TPS (none of the cultivars presented teeth at the petiole sinus) and SH_T_N (all cultivars had two or less consecutive tendrils in the shoot).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Vitamin C content (JU_VC) ranged between 9.7 ± 1.2 (cv. Muscat of Alexandria) and 30.9 ± 0.3 mg/100 mL (Halawani Kanawat), a similar range of variation to that previously reported for a set of autochthonous table grape cultivars from Turkey (Eyduran et al 2015). Besides, some of the qualitative traits analyzed did not show any variance in our set of cultivars: BE_FS (all cultivars were seeded), LE_PSLV (all cultivars presented veins in both sides of the leaf petiole sinus), LE_TPS (none of the cultivars presented teeth at the petiole sinus) and SH_T_N (all cultivars had two or less consecutive tendrils in the shoot).…”
Section: Resultssupporting
confidence: 85%
“…Conscious of the relevance of preserving these invaluable local genetic resources, and looking for the development of better adapted new grapevine cultivars and clones, the Arab Center for the Studies of Arid Zones and Dry lands (ACSAD) established in 1996 a Gene Bank collection in the Jillin Research Station after the prospection of locally-grown traditional varieties. Despite its wide interest, and in contrast to local genetic resources from nearby regions (Aroutiounian et al 2015;Basheer-Salimia et al 2014;Chalak et al 2016;Drori et al 2017;Ekhvaia et al 2014;Ergül et al 2002;Eyduran et al 2015;Fatahi et al 2003;Khadivi-Khub et al 2014;Lamine et al 2014), few local Syrian grapevine cultivars have been adequately described so far (Sawaf et al 1976).…”
Section: Introductionmentioning
confidence: 99%
“…[32] In the literature, only bioactive compounds such as organic acids, sugars and several phenolic compounds were identified in the Igdir ancient grape cultivars. [33] The present investigation is the first study to characterize genetically those ancient grape cultivars and their genetic diversity and relatedness. More data of SSR markers which will provide a noteworthy contribution to the history of the grapevine domestication need to be obtained.…”
Section: Genetic Analysismentioning
confidence: 99%
“…According to Pastrana-Bonilla et al [6], the average concentration of total phenolic compounds in wine grapes is around 2178.8 mg/g gallic acid equivalent, in seeds, 374.6 mg/g gallic acid equivalent, in skins, and 23.8 mg/g gallic acid equivalent, in pulps. In addition, for table grapes, several authors also reported high levels of global and individual phenolic compounds [9]. Also for grape raisins, several works reported high levels of phenolic compounds [10,11].…”
Section: Phenolic Composition Of Wine Grapes and Table Grapesmentioning
confidence: 98%